Seismic acceleration amplification factor for pin supported moment resisting RC frame structures for Chi-Chi earthquake - Agrahari R.K.; Jha I.; Pathak K.K. (My University, 2025)
The Seismic forces, acting on the non-structural component, are different with respect to the lateral force observed by the different design codes. For remarking the behavior of the structural components during dynamic action, large numbers of research were done as compared to the secondary or non-structural components of the structures. The behavior of inertia force acting on the non-structural components changes along with the altitude of the structure. The inertia force existing on non-structural components depends on the acceleration amplification factor. In this paper, five different RC moment-resisting frame models as 2,4,6,8 and 10 stories, with pin support conditions are considered. The linear time history method is used for the analysis of all RC frame models with different range (0.01g to 0.32g) of ground motion data. Determine the acceleration amplification factor for all these models and compared with the previously models. It is observed that no previous model performed satisfactory results. Therefore, to proposed the amplification model which not only depends on the height of the building, natural period of the building but also depends on the range of the Peak Ground Acceleration (PGA).The proposed model is compared with the previous renowned models, It is detected that the proposed model performs better results with respect to other models. © 2022, National Institute of Science Communication and Information Resources. All rights reserved.